Work-related quality of life and its predictors among mining industry workers: a cross-sectional study - Galuh Saraesti Ardhianingrum; Aprilia Alua; Jan Sert; Evan Yulandreano; Ari Prayogo Pribadi; Annisa Utami Rauf; Aris Bastian Lahay (Universitas Gadjah Mada, 2026)
Purpose: This study aimed to examine the associations between Work-Related Quality of Life (WRQoL) domains and overall Quality of Work Life (QoWL) among mining employees and to assess the relative contribution of each domain to QoWL. Methods: A cross-sectional study was conducted among 187 Dump Truck (DT) operators in a coal mining site in East Kalimantan, Indonesia. Data were collected using the standardized WRQoL instrument. QoWL was analyzed as a continuous variable. Bivariate analysis was performed using Pearson correlation, and multivariate analysis was conducted using multiple linear regression to examine the associations between WRQoL domains and QoWL. Results: Five WRQoL domains, consisting of general well–being, home–work interface, job and career satisfaction, control at work, and working conditions, were significantly associated with overall QoWL (all p < 0.001). Stress at work was not significantly associated with QoWL (p = 0.345). In the multivariate model (R² = 0.727), all five domains remained significantly associated with QoWL, with control at work (β = 4.085), job and career satisfaction (β = 3.917), and home–work interface (β = 3.848) demonstrating the strongest relative contributions. Conclusion: QoWL among mining employees is shaped by both structural and psychosocial factors, with work–life balance, autonomy, and career satisfaction playing key roles. These findings highlight the importance of organizational strategies that enhance working conditions, support work–life integration, and promote career development to improve workforce well–being in high-risk industries.